Assessing Self-regulated Learning Skills of Teacher Education Students at VNU University of Education - Ha, Le Thi Hoang (VNU Journal of Science: Education Research; Vol 38 No 2DO - 10.25073/2588-1159/vnuer.4593, 2022)
This article present the output of a quantitative study on self-regulated learning (SRL) of pre-service teacher students at VNU University of Education. Based on a literature review of both theoritical and imperical researches on SRL, a conceptual framework of SRL has been defined for developing a students’self - assessing questionnaire on SRL skills. Data of 809 respondents, who were VNU University of Education’s pre-service teacher students, were analyzed for this report. The outputs of descriptive statistics showed that all the investigated SRL skills of the students were limited, with the average mean scores of four SRL strategies ran between 3 and 4 (within the 1-5 Likert scale) . Among various SRL skills being surveyed, the students assessed themselves better in keeping efforts and being persistent in targeting their study goals. Meanwhiles, a considerable ratio of respondents was reported to be lack of independent learning skills such as setting goals and plans for their own study, self monitoring and regulating their learning techniques. Besides, the percentage of students with limited ambition and self-efficacy in studying was also noteworthy, which may become a warning for various stakeholders, especially the university’s lecturers, the student union and clubs to focus on appropriate solutions and activities to promote students’ SRL.